2007
DOI: 10.1080/09273940701299362
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against Calsequestrin and Type XIII Collagen are Good Markers for Chronic Upper Eyelid Retraction

Abstract: These findings support the notion that autoimmune attack against calsequestrin and collagen XIII in the levator palpebrae superioris (LPS) muscle may play a role in the pathogenesis of upper eyelid retraction and that lid retraction may be the dominant feature of ophthalmopathy in patients with Hashimoto's thyroiditis and non-autoimmune thyroid disease. Because calsequestrin is an intracellular protein, the corresponding autoantibodies probably do not initiate LPS muscle inflammation but may contribute to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Extraocular muscle and orbital adipose tissue expansion results from accumulation of glycosaminoglycans and de novo adipogenesis. 21 The diffuse infiltration of lymphocytes triggered by autoantibodies increases local concentrations of various inflammatory mediators and cytokines, which contribute to the inflammation and subsequent fibrosis of the upper lid retractors. 2,[22][23][24][25][26] Extreme degrees of proptosis may also mechanically exacerbate retraction.…”
Section: Discussionmentioning
confidence: 99%
“…Extraocular muscle and orbital adipose tissue expansion results from accumulation of glycosaminoglycans and de novo adipogenesis. 21 The diffuse infiltration of lymphocytes triggered by autoantibodies increases local concentrations of various inflammatory mediators and cytokines, which contribute to the inflammation and subsequent fibrosis of the upper lid retractors. 2,[22][23][24][25][26] Extreme degrees of proptosis may also mechanically exacerbate retraction.…”
Section: Discussionmentioning
confidence: 99%
“…While the extra ocular muscle reaction, which can occur in the absence of OCT and fat inflammation, may be a separate TAO subtype [10,11], it has not been shown conclusively that the two types differ from Nunery types 1 (mainly involving the orbital fat without restrictive myopathy) and 2 (with diplopia and restrictive myopathy) [12]. Earlier, we showed that chronic UER can be the dominant or only eye sign, except for mild proptosis, in patients with Graves Disease (GD), Hashimoto thyroiditis and transient (sub acute, silent) thyroiditis [13].…”
Section: Introductionmentioning
confidence: 92%
“…Many workers have investigated the possible existence of auto antigens that are expressed in both the thyroid and orbit [5,[13][14][15]. Such antigens include the TSHR [7,8,16], the 64-kDa protein, now identified as the Flavoprotein (Fp) sub-unit succinate dehydrogenase [17] or some other, as yet unidentified, thyroid and eye muscle shared cell membrane antigen.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Serum antibodies to collagen XIII have been found to be associated with TAO. [4][5][6] However, the disease specificity and sensitivity of these auto-antibodies for TAO, and whether they are primary or secondary to the pathogenesis, is yet to be established.…”
Section: Introductionmentioning
confidence: 99%